Biomechanically driven unsteady non-uniform flow of Copper water and Silver water nanofluids through finite length channel. (July 2017) - Akbar, Noreen Sher; Butt, Adil Wahid; Tripathi, Dharmendra
Highlights: Unsteady flow is considered. Analysis is done in non-Uniform channel. Copper water and Silver water nanofluids are discussed. Pressure gradient is evaluated. Exact solutions are presented. Abstract: Background and objectives: This paper aims to investigate the unsteady flow of two types of nanofluids i.e Copper water nanofluids and Silver water nanofluids) through finite length non-uniform channel driven by peristaltic sinusoidal wave propagations. Methods: The governing equations are reduced in linear form using dimensional analysis and considering the low Reynolds number and large wavelength approximations. The time dependent temperature field, axial velocity, transverse velocity and pressure difference are obtained analytically in closed form solution. Trapping phenomenon is also discussed with the help of contour plots of stream function. A comparative study of pure water (Newtonian fluid), Copper water nanofluids and Silver water nanofluids under the influence of relevant physical parameters is made in graphical form and also discussed. The effects of absorption parameter and Grashof number on velocity profiles, temperature profiles and pressure distribution along the length of channel are examined. Results conclusions: The computational results reveal that the velocity profile is maximum for Silver water nanofluids however, it is least for Copper water nanofluids. It is also concluded the temperature profile is more for pure water in comparison to Silver water and Copper water nanofluids. This model is applicable to design, micro-peristaltic pumps which help in Nanoparticle-based targeted drug delivery and to transport the sensitive or corrosive fluids, sanitary fluids, slurries and noxious fluids in nuclear industry.